DEVELOPMENT TRENDS IN THE STRUCTURE OF SERVICES OF THE PUBLIC POSTAL OPERATOR IN SERBIA - Dobrodolac, Momčilo; Blagojevic, Mladenka; Draskovic, Darko; Švadlenka, Libor (Scientific Research Center Ltd., 2018)
A public postal operator represents some of the largest and most important infrastructures in each country. Since most postal markets are very competitive, there is a clear need for redefining and modernizing the existing service portfolio of public postal operator. Many researchers estimate that traditional postal services will lose their usefulness. However, this should be investigated based on the real data which is done in this paper. The next question is what is the role of new services based on electronic, Internet and communication technologies. This paper analyzes the development trends related to the universal service obligation and commercial services. The research is based on the ratio of the volume of services and achieved revenue in the case of public postal operator of the Republic of Serbia. Based on the conducted analysis, the operator could form an adequate business strategy.
Trendy ve struktuře služeb veřejného poštovního operátora v Srbsku
Keywords: public postal operator; structure of services; revenue; strategy; veřejný poštovní operátor; struktura služeb; příjmy; strategie